Composition of superabsorbent polymer and method for preparing same
By introducing diester compounds into the surface crosslinking layer of superabsorbent polymers and combining other deodorants, the problem that superabsorbent polymers in the prior art is difficult to suppress multiple odors in sanitary products, and excellent deodorization and absorption performance are achieved.
Patent Information
- Application Number
- CN202380053116.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-16
- Filing Date
- 2023-12-26
- Publication Date
- 2025-02-28
AI Technical Summary
When used in sanitary products, it is difficult to effectively suppress various odors produced by absorbed liquids, and the deodorization performance is insufficient.
By introducing diester compounds into the surface crosslinking layer of the superabsorbent polymer, and combining chelating agents, iodine compounds and organic acids as deodorants, a superabsorbent polymer composition with excellent deodorization ability is formed.
Superabsorbent polymers are achieved with excellent deodorization ability in sanitary products, while maintaining their efficient absorption and water retention ability.
Smart Images

Figure BDA0005236785490000021 
Figure BDA0005236785490000031 
Figure BDA0005236785490000071
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0020907 filed on February 16, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a super absorbent polymer composition and a method for preparing the same. More particularly, the present invention relates to a super absorbent polymer composition having deodorizing ability and a method for preparing the same. Background Art
[0004] Super absorbent polymer (SAP) is a synthetic polymer material that can absorb 500 to 1000 times its own weight of water. Depending on the company that developed it, it is also called super absorbent material (SAM), absorbent gel material (AGM), etc. Super absorbent polymers were first commercialized as sanitary products. At present, in addition to sanitary products such as disposable diapers for children, they are also widely used as soil water retention materials, water-stopping materials for civil engineering and construction, sheets for seedling cultivation, fresh-keeping preservatives in the field of food circulation, and dressing materials.
[0005] In most cases, such superabsorbent polymers are widely used in the field of sanitary products such as diapers or sanitary pads. In sanitary products, superabsorbent polymers are generally contained in pulp in a spread state. However, recently, in order to provide sanitary products such as diapers with a thinner thickness, diapers with reduced pulp content, or even pulp-free diapers that do not use pulp at all, are being actively developed.
[0006] Therefore, in the case of sanitary products with reduced pulp or pulp-free sanitary products, superabsorbent polymers are contained at a relatively high ratio, and such superabsorbent polymer particles are inevitably contained in multiple layers. The superabsorbent polymer should basically exhibit high absorption performance and absorption speed so that all superabsorbent polymer particles contained in the multiple layers can more effectively absorb liquids such as urine. In addition, the absorbed liquid should not leak even under external pressure, and furthermore the superabsorbent polymer should have permeability so as to appropriately maintain the original shape even when it absorbs liquid and swells.
[0007] Therefore, many studies are being conducted, such as surface cross-linking, to improve basic absorption and water retention capabilities.
[0008] However, superabsorbent polymers can be used for sanitary articles, and in this case, the feeling during use may be deteriorated due to the odor of the absorbed liquid (such as excrement of humans and pets). In particular, it is necessary to suppress the odor generated by the absorbed liquid.
[0009] Therefore, previously, adding organic acids or antibacterial substances as deodorants was considered to impart deodorizing properties to superabsorbent polymers, but in fact, the odor generated by the absorbed liquid is not limited to ammonia, but is generated by various substances, so it is difficult to suppress the odor using only one substance such as organic acids or antibacterial substances.
[0010] Therefore, the demand for odor suppression as well as basic properties of super absorbent polymers including absorption capacity and water retention capacity is gradually increasing. Therefore, it is necessary to prepare super absorbent polymers excellent in deodorizing ability. Summary of the invention
[0011] [Technical issues]
[0012] The object of the present invention is to provide a superabsorbent polymer composition having deodorizing ability and a preparation method thereof.
[0013] More particularly, an object of the present invention is to provide a superabsorbent polymer composition having excellent deodorizing ability and minimizing performance degradation, and a method for preparing the same.
[0014] [Technical solution]
[0015] In order to solve the above-mentioned object, a superabsorbent polymer composition is provided according to the present invention, comprising:
[0016] A superabsorbent polymer comprising a base resin and a surface crosslinked layer formed on the surface of the base resin, the base resin comprising a crosslinked polymer formed by crosslinking polymerization of an acrylic monomer having an at least partially neutralized acid group and an internal crosslinking agent, wherein the crosslinked polymer in the surface crosslinked layer is additionally crosslinked by the surface crosslinking agent; and a diester compound represented by the following Chemical Formula 1,
[0017] The diester compound is contained in the surface cross-linked layer of the super absorbent polymer and / or is separated from the super absorbent polymer:
[0018] [Chemical formula 1]
[0019]
[0020] In Chemical Formula 1, n is an integer from 1 to 10, and
[0021] R is C 1-20 Straight chain or branched alkyl.
[0022] According to the present invention, there is also provided a method for preparing a superabsorbent polymer composition, which comprises the following steps:
[0023] In the presence of an internal crosslinking agent and a polymerization initiator, an acrylic monomer having an acid group that is at least partially neutralized is crosslinked and polymerized to form a hydrogel polymer (step 1);
[0024] drying and grinding the hydrogel polymer to prepare a base resin comprising a cross-linked polymer (step 2);
[0025] mixing a surface cross-linking agent with the base resin to prepare a mixture (step 3); and
[0026] heat-treating the mixture to prepare a super absorbent polymer having a surface cross-linked layer formed on the surface of the base resin (step 4),
[0027] Wherein a diester compound represented by the following Chemical Formula 1 is contained during and / or after the surface cross-linking reaction:
[0028] [Chemical formula 1]
[0029]
[0030] In Chemical Formula 1, n is an integer from 1 to 10, and
[0031] R is C 1-20 Straight chain or branched alkyl.
[0032] [Beneficial Effects]
[0033] As described above, the present invention provides a super absorbent polymer composition having not only excellent deodorizing ability but also retaining excellent absorption performance by applying a diester compound to the super absorbent polymer and a method for preparing the same. DETAILED DESCRIPTION
[0034] The terms used herein are only used to explain specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, singular expressions include their plural expressions. Throughout the specification, the terms "comprising", "equipped with" or "having" etc. are intended to indicate the presence of implemented features, numbers, steps, structural components or combinations thereof, and they are not intended to exclude the possibility of the presence or addition of one or more other features, numbers, steps, structural components or combinations thereof.
[0035] Although the present invention can be modified in many ways and the present invention can have various forms, specific embodiments will be described and explained in detail below. However, it should be understood that this is not intended to limit the present invention to the specific disclosure, and the present invention includes all modifications, equivalents or replacements thereof without departing from the spirit and technical scope of the present invention.
[0036] Hereinafter, a preparation method of a super absorbent polymer and a super absorbent polymer according to specific embodiments of the present invention will be described in detail.
[0037] Hereinafter, the technical terms used herein are used only to refer to specific embodiments, and they are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression used herein may include a plural expression.
[0038] For reference, as used herein, "superabsorbent polymer" may mean superabsorbent polymer itself, or it may be used to include polymers suitable for production made by additional processes (e.g., surface crosslinking, fine powder reconstitution, drying, grinding, classification, etc.) depending on the context.
[0039] Furthermore, as used herein, "base resin" or "base resin powder" refers to particles or powders obtained by drying and grinding a polymer polymerized from an acrylic monomer before undergoing a surface modification or surface crosslinking step as described later.
[0040] (Composition of superabsorbent polymer)
[0041] According to one embodiment of the present invention, a superabsorbent polymer composition is provided.
[0042] The superabsorbent polymer composition comprises: a superabsorbent polymer comprising a base resin and a surface crosslinked layer formed on the surface of the base resin, the base resin comprising a crosslinked polymer formed by crosslinking polymerization of an acrylic monomer having an at least partially neutralized acid group and an internal crosslinking agent, wherein the crosslinked polymer in the surface crosslinked layer is additionally crosslinked by the surface crosslinking agent; and a diester compound,
[0043] The diester compound is contained in the surface cross-linked layer of the super absorbent polymer and / or is separated from the super absorbent polymer.
[0044] The acrylic monomer may be any monomer commonly used in preparing superabsorbent polymers. As a non-limiting example, the acrylic monomer may be a compound represented by the following Chemical Formula 2:
[0045] [Chemical formula 2]
[0046] R 1 -COOM1
[0047] In chemical formula 2,
[0048] R1 is a C2-5 alkyl group containing an unsaturated bond,
[0049] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0050] Preferably, the monomer may be one or more selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0051] The acrylic monomer may have an acid group, and at least a portion of the acid group may be neutralized. Preferably, a monomer partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. may be used.
[0052] Wherein, the neutralization degree of the monomer may be 40 mol% to 95 mol%, or 40 mol% to 80 mol%, or 45 mol% to 75 mol%. Although the range of the neutralization degree may vary depending on the final performance, if the neutralization degree is too high, the neutralized monomer may precipitate, and thus it may be difficult to smoothly polymerize, whereas if the neutralization degree is too low, the absorption power of the polymer may be significantly reduced, and may exhibit an elastic rubber-like property that is difficult to handle.
[0053] Meanwhile, in order to improve the properties of the polymer polymerized from the acrylic monomer, the polymerization is carried out in the presence of a crosslinking agent ("internal crosslinking agent") This crosslinking agent is used for internal crosslinking of the hydrogel polymer and can be used separately from the "surface crosslinking agent" described later.
[0054] As the internal crosslinking agent, any compounds may be used as long as they are capable of introducing crosslinking during the polymerization of the acrylic monomer. As a non-limiting example, as the internal crosslinking agent, a multifunctional crosslinking agent such as N,N′-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, 1,2-butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triallylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate may be used alone or in combination, but is not limited thereto.
[0055] Such an internal crosslinking agent may be used at a concentration of 0.001 wt % to 1 wt % or 0.01 wt % to 0.8 wt % or 0.1 wt % to 0.7 wt % based on the monomer composition. If the concentration of the internal crosslinking agent is too low, the absorption rate of the polymer may decrease and the gel strength may become weak. On the contrary, if the concentration of the internal crosslinking agent is too high, the absorption capacity of the superabsorbent polymer may decrease, and thus it may not be preferred as an absorbent.
[0056] In addition, the monomer composition may further contain additives such as a plasticizer, an antiseptic stabilizer, an antioxidant, etc. as needed.
[0057] The surface crosslinked layer is formed by additional crosslinking of the crosslinked polymer by a surface crosslinking agent, wherein the surface crosslinking agent is not particularly limited as long as it is generally used for surface crosslinking of superabsorbent polymers and is a compound capable of reacting with a functional group of the polymer.
[0058] Preferably, in order to improve the properties of the prepared superabsorbent polymer, as a surface crosslinking agent, one or more selected from the group consisting of polyol compounds, epoxy compounds, polyamine compounds, halogenated epoxy compounds, condensation products of halogenated epoxy compounds, oxazoline compounds, monooxazolidinone compounds, dioxazolidinone compounds or polyoxazolidinone compounds, cyclic urea compounds, polyvalent metal salts and alkylene carbonate compounds can be used.
[0059] In particular, as examples of the polyol compound, one or more selected from the group consisting of monoethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol or polyethylene glycol, monopropylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,2-cyclohexanedimethanol can be used.
[0060] Furthermore, as the epoxy compound, ethylene glycol diglycidyl ether, glycidol, etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneamine, and polyamidepolyamine can be used.
[0061] Furthermore, as the halogenated epoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, and as the monooxazolidinone compound, dioxazolidinone compound, or polyoxazolidinone compound, for example, 2-oxazolidinone and the like can be used.
[0062] In addition, as the alkylene carbonate compound, ethylene carbonate and the like can be used. These compounds can be used alone or in combination. Meanwhile, in order to improve the efficiency of the surface crosslinking process, one or more C2-10 polyol compounds can be included in these surface crosslinking agents.
[0063] The content of the added surface crosslinking agent can be appropriately selected according to the type of the added surface crosslinking agent and the reaction conditions, but generally, based on 100 parts by weight of the polymer, its amount can be from about 0.001 parts by weight to about 5 parts by weight, preferably from about 0.01 parts by weight to about 3 parts by weight, and more preferably from about 0.05 parts by weight to about 2 parts by weight.
[0064] If the content of the surface crosslinking agent is too small, the surface crosslinking reaction may be difficult to occur, and if the content is greater than 5 parts by weight based on 100 parts by weight of the polymer, the absorption capacity and performance may be reduced due to excessive progress of the surface crosslinking reaction.
[0065] Meanwhile, inorganic materials can be further included in the surface crosslinking agent. As such inorganic materials, one or more of the group selected from silicon dioxide, clay, aluminum oxide, silicon dioxide-alumina composite material, titanium dioxide, zinc oxide and aluminum sulfate can be used. The inorganic material can be used in the form of powder or liquid, particularly aluminum oxide powder, silicon dioxide-alumina powder, titanium dioxide powder or nano silicon dioxide solution. Based on the base resin of 100 weight parts, the usage amount of the inorganic material can be from about 0.001 weight part to about 1 weight part.
[0066] The composition of the super absorbent polymer according to one embodiment of the present invention may contain a diester compound as a deodorizing substance. Since the ester and hydrophobic functional groups of the diester compound have affinity with malodorous substances, when the super absorbent polymer composition containing the diester compound is applied to sanitary products, the odor of the liquid absorbed in the sanitary products can be removed. In one embodiment of the present invention, the diester compound can be represented by the following chemical formula 1.
[0067] [Chemical formula 1]
[0068]
[0069] In Chemical Formula 1, n may be an integer of 1 to 10, for example, an integer of 2 to 4.
[0070] R can be C 1-20 In particular, R can be C 3-4 Straight chain or branched alkyl. For example, R can be isopropyl or isobutyl.
[0071] The diester compound may be contained in the surface cross-linked layer of the super absorbent polymer and / or separated from the super absorbent polymer. The diester compound contained separately from the super absorbent polymer means that the diester compound is mixed with the super absorbent polymer having the surface cross-linked layer, so the diester compound exists on the outer surface of the surface cross-linked layer rather than inside the surface cross-linked layer.
[0072] The diester compound may include one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate, diisobutyl glutarate and diisobutyl adipate. In particular, the diester compound may include one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate and diisobutyl adipate.
[0073] Based on 100 parts by weight of the base resin, the content of the diester compound may be 0.1 to 5.0 parts by weight. In particular, based on 100 parts by weight of the base resin, the content of the diester compound may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, or 0.4 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, 1.0 parts by weight or less, or 0.5 parts by weight or less.
[0074] In order to exhibit a target level of deodorizing ability while maintaining the unique absorption properties of the super absorbent polymer, in the present invention, it is preferred that the content of the diester compound as the deodorizing substance is within the above range.
[0075] The superabsorbent polymer composition may further include one or more additives selected from the group consisting of a chelating agent, an iodine-based compound, and an organic acid.
[0076] The composition of the superabsorbent polymer may contain a chelating agent. In the case of sanitary products containing the superabsorbent polymer composition, bacteria originating from the skin and the like may meet the absorbed liquid, thereby additionally generating odor through bacterial growth, but the chelating agent may inhibit such bacterial growth.
[0077] The chelating agent may include a glycine (or salt) chelating agent. In particular, the glycine (or salt) chelating agent may include one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetate (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof. More particularly, the chelating agent may be ethylenediaminetetraacetic acid (EDTA).
[0078] In particular, aminoacetate chelating agents can effectively inhibit the growth of bacteria (such as E. coli) caused by odor-generating substances. As the wearing time of the product passes, the bacterial growth is accelerated by the odor-generating substances remaining in the product, thus generating additional odor, but aminoacetate chelating agents can inhibit this bacterial growth, thereby effectively reducing the generation of additional odor.
[0079] In particular, aminoacetate (or salt) chelators can capture multivalent metal components required for cell membrane growth and development, thereby effectively inhibiting bacterial growth.
[0080] The content of the chelating agent may be 0.1 to 2.0 parts by weight based on 100 parts by weight of the base resin. In particular, the content of the chelating agent may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 2.0 parts by weight or less, 1.5 parts by weight or less, or 1.0 parts by weight or less, based on 100 parts by weight of the base resin.
[0081] When used within the above content range, effective bacteria inhibition performance can be achieved without deteriorating the unique absorption performance of the super absorbent polymer, thereby significantly improving the deodorizing ability of the super absorbent polymer.
[0082] The chelating agent may be mixed in an aqueous solution in the form of a salt and used, and therefore the above content range is based on the solid content.
[0083] The composition of the superabsorbent polymer may contain an iodine compound. The iodine compound may be a metal iodide salt. The metal iodide salt may be added during the preparation process in the form of one or more selected from the group consisting of CuI, NaI and KI and I2 dissolved in water together, or in the form of a powder obtained by drying an aqueous solution. The metal iodide salt may be added to the superabsorbent polymer together with a diester compound to impart deodorizing properties. The metal iodide salt acts on most malodorous substances and generally acts by oxidizing the malodorous substances to remove them.
[0084] Based on 100 parts by weight of the base resin, the content of the iodine compound may be 0.1 to 5.0 parts by weight. In particular, based on 100 parts by weight of the base resin, the content of the iodine compound may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, or 1.0 parts by weight or less.
[0085] The composition of the superabsorbent polymer may contain an organic acid. The organic acid may be one or more selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid, and propionic acid. In particular, the organic acid may be citric acid. The organic acid may exhibit a deodorizing effect in the superabsorbent polymer together with the diester compound.
[0086] The content of the organic acid may be 0.1 to 5.0 parts by weight based on 100 parts by weight of the base resin. In particular, the content of the organic acid may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, or 1.0 parts by weight or less, based on 100 parts by weight of the base resin.
[0087] (Method for preparing superabsorbent polymer composition)
[0088] According to one embodiment of the present invention, a method for preparing a superabsorbent polymer composition is provided.
[0089] The method for preparing a composition of a superabsorbent polymer comprises the following steps:
[0090] In the presence of an internal crosslinking agent and a polymerization initiator, an acrylic monomer having an acid group that is at least partially neutralized is crosslinked and polymerized to form a hydrogel polymer (step 1);
[0091] drying and grinding the hydrogel polymer to prepare a base resin comprising a cross-linked polymer (step 2);
[0092] mixing a surface cross-linking agent with the base resin to prepare a mixture (step 3); and
[0093] heat-treating the mixture to prepare a super absorbent polymer having a surface cross-linked layer formed on the surface of the base resin (step 4),
[0094] The diester compound is contained during and / or after the surface cross-linking reaction.
[0095] The method for preparing the super absorbent polymer mainly comprises the steps of polymerizing acrylic monomers to prepare a hydrogel polymer and grinding the same. In addition, in order to improve various properties of the super absorbent polymer, the surface of the prepared super absorbent polymer is cross-linked.
[0096] In the present invention, a diester compound is mixed with a surface-crosslinked superabsorbent polymer to provide a composition of a superabsorbent polymer having a deodorizing property.
[0097] Meanwhile, the expression "mixed in step A" means additionally mixing with the target mixture while performing step A, and may also mean mixing in multiple times according to the target content ratio in the corresponding step. Meanwhile, the expression "mixed before and after step A" means additionally mixing before performing step A or after completing step A.
[0098] Hereinafter, the present invention will be described in detail according to the steps.
[0099] (Step 1)
[0100] Step 1 is a step of preparing a hydrogel polymer, and in particular, in this step, a monomer composition including an acrylic monomer having an at least partially neutralized acid group is cross-linked and polymerized to form a hydrogel polymer.
[0101] The acrylic monomer may be any monomer commonly used in the preparation of superabsorbent polymers. In particular, the acrylic monomer may be a compound represented by the following Chemical Formula 2:
[0102] [Chemical formula 2]
[0103] R 1 -COOM 1
[0104] In chemical formula 2,
[0105] R 1 is a C2-5 alkyl group containing an unsaturated bond,
[0106] M 1 It is a hydrogen atom, a monovalent or divalent metal, an ammonium group or an organic amine salt.
[0107] Preferably, the monomer may be one or more selected from the group consisting of acrylic acid, methacrylic acid, and monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts thereof.
[0108] The acrylic monomer may have an acid group, and at least a portion of the acid group may be neutralized. Preferably, a monomer partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, etc. may be used.
[0109] Wherein, the neutralization degree of the monomer may be 40 mol% to 95 mol%, or 40 mol% to 80 mol%, or 45 mol% to 75 mol%. Although the range of the neutralization degree may vary depending on the final performance, if the neutralization degree is too high, the neutralized monomer may precipitate, and thus it may be difficult to smoothly polymerize, whereas if the neutralization degree is too low, the absorption power of the polymer may be significantly reduced, and may exhibit an elastic rubber-like property that is difficult to handle.
[0110] In the monomer composition, a polymerization initiator generally used for preparing a super absorbent polymer may be included.
[0111] As the polymerization initiator, a thermal polymerization initiator or a photopolymerization initiator may be used according to the polymerization method. However, even when photopolymerization is performed, since a certain amount of heat is generated by UV irradiation or the like, and a certain degree of heat is generated according to the progress of the exothermic polymerization reaction, a thermal polymerization initiator may be additionally contained.
[0112] As the photopolymerization initiator, one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyalkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine and α-amino ketone can be used. Among them, as a specific example of acyl phosphine, commercially available Lucrin TPO, i.e. 2,4,6-trimethyl-benzoyl-trimethylphosphine oxide, can be used. More various photopolymerization initiators are described in Reinhold Schwalm's "UV Coatings: Basics, Recent Developments and New Applications" on page 115, which can be used as a reference.
[0113] As a thermal polymerization initiator, one or more selected from the group consisting of persulfate initiators, azo initiators, hydrogen peroxide and ascorbic acid can be used. Specific examples of persulfate initiators can include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), ammonium persulfate (NH4)2S2O8), etc., and specific examples of azo initiators can include 2,2-azobis (2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene) isobutylamidine dihydrochloride, 2-(carbamoyl azo) isobutyronitrile, 2,2-azobis [2-(2-imidazoline-2-yl) propane] dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More various thermal polymerization initiators are described in Odian's "Principles of Polymerization (Wiley, 1981)" on page 203, which can be used as a reference.
[0114] Such a polymerization initiator may be added at a concentration of 0.001 wt % to 1 wt % or 0.005 wt % to 0.1 wt % based on the monomer composition. If the concentration of the polymerization initiator is too low, the polymerization rate may be slowed down, and a large amount of residual monomers may be extracted in the final product. Also, if the concentration of the polymerization initiator is too high, the polymer chains constituting the superabsorbent polymer network may become shorter, and thus, the extractable content may increase, and the superabsorbent polymer pressure absorption rate may decrease, thereby deteriorating the performance of the polymer.
[0115] Meanwhile, in order to improve the properties of the polymer polymerized from the acrylic monomer, the polymerization of the monomer composition is carried out in the presence of a crosslinking agent ("internal crosslinking agent"). The crosslinking agent is used for internal crosslinking of the hydrogel polymer and can be used separately from the "surface crosslinking agent" described later.
[0116] As the internal crosslinking agent, any compounds may be used as long as they are capable of introducing crosslinking during the polymerization of the acrylic monomer. As a non-limiting example, as the internal crosslinking agent, a multifunctional crosslinking agent such as N,N′-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, 1,2-butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerol tri(meth)acrylate, pentaerythritol tetraacrylate, triallylamine, allyl (meth)acrylate, ethylene glycol diglycidyl ether, propylene glycol, glycerol or ethylene carbonate may be used alone or in combination, but is not limited thereto.
[0117] Such an internal crosslinking agent may be used at a concentration of 0.001 wt % to 1 wt % or 0.01 wt % to 0.8 wt % or 0.1 wt % to 0.7 wt % based on the monomer composition. If the concentration of the internal crosslinking agent is too low, the absorption rate of the polymer may decrease and the gel strength may become weak. On the contrary, if the concentration of the internal crosslinking agent is too high, the absorption capacity of the superabsorbent polymer may decrease, and thus it may not be preferred as an absorbent.
[0118] In addition, the cross-linking polymerization of the monomer composition may be performed in the presence of a foaming agent according to the necessity and degree of improving the absorption rate. Such a foaming agent may be decomposed during the cross-linking polymerization reaction to generate a gas, thereby forming pores in the hydrogel polymer. Therefore, when such a foaming agent is additionally used, a more developed porous structure is formed in the super absorbent polymer, and thus, the absorption rate of the super absorbent polymer can be further improved.
[0119] As a non-limiting example, the foaming agent may include one or more compounds selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, magnesium carbonate, azodicarbonamide (ADCA), dinitrosopentamethylenetetramine (DPT), p,p'-oxybis(benzenesulfonylhydrazide) (OBSH), p-toluenesulfonylhydrazide (TSH), sucrose stearate, sucrose palmitate, and sucrose laurate.
[0120] The blowing agent may be included in an amount of 1000 ppmw to 4000 ppmw in the monomer composition, and more particularly, the amount is 1000 ppmw or more, 1100 ppmw or more, or 1200 ppmw or more, and 4000 ppmw or less, or 3500 ppmw or less, or 3000 ppmw or less.
[0121] Furthermore, the monomer composition may contain a plasticizer, an antiseptic stabilizer, an antioxidant, and the like as necessary.
[0122] In addition, the monomer composition may be prepared in the form of a solution in which the above-mentioned raw materials, including acrylic monomers, polymerization initiators, internal cross-linking agents, foaming agents, etc., are dissolved in a solvent.
[0123] Among them, the solvent that can be used is not limited as long as it can dissolve the above raw materials. For example, as the solvent, water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, N,N-dimethylacetamide or a mixture thereof can be used.
[0124] The formation of the hydrogel polymer by polymerization of the monomer composition may be performed by a common polymerization method, and the process is not particularly limited.
[0125] As a non-limiting example, polymerization methods are roughly divided into thermal polymerization and photopolymerization according to the kind of energy source, and thermal polymerization can be performed in a reactor equipped with a stirring shaft (such as a kneader) and photopolymerization can be performed in a reactor equipped with a movable conveyor belt.
[0126] For example, the hydrogel polymer can be obtained by adding the above-mentioned monomer composition to a reactor (e.g., a kneader equipped with a stirring shaft) and supplying hot air or heating the reactor to perform thermal polymerization. The hydrogel polymer discharged to the reactor outlet can have a size of several millimeters to several centimeters according to the shape of the stirring shaft equipped in the reactor. In particular, the size of the obtained hydrogel polymer can vary according to the concentration and addition rate of the added monomer composition, and a hydrogel polymer with a particle size of 2 mm to 50 mm can usually be obtained.
[0127] For another example, in the case of photopolymerization of the monomer composition in a reactor equipped with a movable conveyor as described above, a hydrogel polymer in the form of a sheet can be obtained. The thickness of the sheet can vary depending on the concentration and addition rate of the added monomer composition, but it is generally preferred that the thickness of the sheet be controlled to be 0.5 cm to 10 cm so that the entire sheet can be polymerized uniformly and at the same time ensure production speed, etc.
[0128] The hydrogel polymer thus obtained may have a water content of 40% to 80% by weight. Wherein, "water content" refers to the content of water in the total weight of the hydrogel polymer, and refers to the value obtained by subtracting the weight of the dry polymer from the weight of the hydrogel polymer. In particular, it is defined as a value calculated by measuring the weight loss based on the evaporation of water in the polymer while raising the temperature of the polymer by infrared heating to dryness. Wherein, the temperature is raised from room temperature to about 180°C and then maintained at 180°C, and the total drying time can be set to 20 minutes, including a 5-minute heating step.
[0129] (Step 2)
[0130] Step 2 of the present invention is a step of drying and grinding the hydrogel polymer prepared in step 1 to form a base resin.
[0131] In particular, in order to improve the drying efficiency of the hydrogel polymer, affect the morphology of the superabsorbent polymer, and thus affect various properties of the superabsorbent polymer, including the absorption rate, and in particular to improve the absorption rate of the superabsorbent polymer, the present invention may further include a coarse grinding step before drying the hydrogel polymer. Hereinafter, in order to distinguish it from the grinding after drying, for the sake of convenience, the grinding before drying is referred to as "coarse grinding" herein.
[0132] The grinding machine used for grinding is not limited, and specifically, may include any one selected from the group consisting of a vertical mill, a turbine cutter, a turbine grinder, a rotary cutter, a cutter, a disc mill, a pulverizing crusher, a crusher, a shredder and a disc cutter, but is not limited thereto.
[0133] Among them, the rough grinding step may be performed so that the particle size of the hydrogel polymer may become about 2 mm to about 10 mm. Due to the high water content of the hydrogel polymer, grinding to a particle size of less than 2 mm is technically not easy, and it may cause aggregation between the ground particles. Meanwhile, if the grinding to a particle size greater than 10 mm, the effect of improving the efficiency of the subsequent drying step may not be significant.
[0134] Drying can be performed at a temperature of 120°C to 250°C, 140°C to 200°C, or 150°C to 190°C. The drying temperature can be defined as the temperature of the heat transfer medium supplied for drying or the temperature inside the drying reactor containing the heat transfer medium and the polymer during the drying process. If the drying temperature is too low and the drying time is prolonged, the process efficiency will be reduced. Therefore, in order to prevent this, the drying temperature is preferably above 120°C. In addition, if the drying temperature is higher than the required temperature, the surface of the hydrogel polymer may be over-dried, so the generation of fine powder may increase in the subsequent grinding step, and the properties of the final polymer may be deteriorated. Therefore, in order to prevent this, the drying temperature is preferably below 250°C.
[0135] The drying time in the drying step is not particularly limited, but can be controlled to be 20 minutes to 90 minutes at the above drying temperature in consideration of the processing efficiency and performance of the polymer.
[0136] Drying can be performed using common media, for example, drying can be performed by supplying hot air, infrared radiation, microwave radiation or UV radiation to the ground hydrogel polymer or the like.
[0137] In addition, preferably, drying is performed so that the water content of the dried polymer can be 0.1 wt % to 10 wt %. That is, in the case where the water content of the dried polymer is less than 0.1 wt %, the production cost may increase and the cross-linked polymer may deteriorate due to excessive drying. In addition, if the water content of the dried polymer is greater than 10 wt %, defects may occur in subsequent processes.
[0138] Subsequently, the dried hydrogel polymer may be ground. This is a step to optimize the surface area of the base resin powder and the superabsorbent polymer. The grinding may be performed so that the particle size of the ground polymer may become 150 μm to 850 μm.
[0139] Among them, as the grinder, a common grinder such as a pin grinder, a hammer grinder, a spiral grinder, a roller grinder, a disc grinder, a tumble grinder, etc. can be used.
[0140] Furthermore, in order to control the properties of the finally produced super absorbent polymer, particles having a particle size of 150 μm to 850 μm among the polymer particles obtained through the grinding step are subjected to a step of selectively classifying.
[0141] The base resin can be obtained by the classification step. The base resin may have a particle size of 150 μm to 850 μm, and may contain fine powder having a particle size of less than 150 μm at a content of 2 wt % or less or 1 wt % or less.
[0142] In addition, after drying and grinding to obtain the base resin powder, a step of mixing zirconium phosphate may be performed. The zirconium phosphate may be premixed. That is, the zirconium phosphate may be mixed with the base resin as a solid by a dry physical method before surface crosslinking. Zirconium phosphate is a substance that can physically adsorb malodorous substances. Therefore, by further mixing zirconium phosphate with the base resin powder, an additional deodorizing effect may be obtained.
[0143] Among them, based on 100 parts by weight of the base resin, the content of zirconium phosphate can be 5.0 parts by weight or less. It is used to additionally increase the deodorizing ability and may not contain it, but in the case of containing zirconium phosphate, based on 100 parts by weight of the base resin, the content of zirconium phosphate can be specifically 0.5 parts by weight or more, 0.8 parts by weight or more, 1.0 parts by weight or more, 1.3 parts by weight or more, 1.5 parts by weight or more, or 1.8 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, or 2.0 parts by weight or less. If too little zirconium phosphate is mixed, the deodorizing effect obtained thereby may not be significant, and if too much zirconium phosphate is included, surface crosslinking may not be properly achieved, and therefore, absorbency under pressure, etc. may deteriorate.
[0144] (Step 3)
[0145] Step 3 of the present invention is a step of mixing a surface crosslinking agent with the base resin powder prepared in step 2.
[0146] The surface crosslinking composition used in step 3 comprises a surface crosslinking agent, and the surface crosslinking agent is not particularly limited as long as it is commonly used for surface crosslinking of super absorbent polymers and is a compound capable of reacting with functional groups of polymers.
[0147] Preferably, in order to improve the properties of the prepared superabsorbent polymer, as a surface crosslinking agent, one or more selected from the group consisting of polyol compounds, epoxy compounds, polyamine compounds, halogenated epoxy compounds, condensation products of halogenated epoxy compounds, oxazoline compounds, monooxazolidinone compounds, dioxazolidinone compounds or polyoxazolidinone compounds, cyclic urea compounds, polyvalent metal salts and alkylene carbonate compounds can be used.
[0148] In particular, as examples of the polyol compound, one or more selected from the group consisting of monoethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol or polyethylene glycol, monopropylene glycol, 1,3-propylene glycol, dipropylene glycol, 2,3,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerol, polyglycerol, 2-butene-1,4-diol, 1,4-butanediol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol and 1,2-cyclohexanedimethanol can be used.
[0149] Furthermore, as the epoxy compound, ethylene glycol diglycidyl ether and glycidol etc. can be used, and as the polyamine compound, one or more selected from the group consisting of ethylenediamine, diethylenetriamine, triethylenetriamine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine and polyamidepolyamine can be used.
[0150] Furthermore, as the halogenated epoxy compound, epichlorohydrin, epibromohydrin, and α-methylepichlorohydrin can be used, and as the monooxazolidinone compound, dioxazolidinone compound, or polyoxazolidinone compound, for example, 2-oxazolidinone and the like can be used.
[0151] In addition, as the alkylene carbonate compound, ethylene carbonate and the like can be used. These compounds can be used alone or in combination. Meanwhile, in order to improve the efficiency of the surface crosslinking process, one or more C2-10 polyol compounds can be included in these surface crosslinking agents.
[0152] The content of the added surface crosslinking agent can be appropriately selected according to the type of the added surface crosslinking agent and the reaction conditions, but generally, based on 100 parts by weight of the polymer, its amount can be from about 0.001 parts by weight to about 5 parts by weight, preferably from about 0.01 parts by weight to about 3 parts by weight, and more preferably from about 0.05 parts by weight to about 2 parts by weight.
[0153] If the content of the surface crosslinking agent is too small, the surface crosslinking reaction may be difficult to occur, and if the content is greater than 5 parts by weight based on 100 parts by weight of the polymer, the absorption capacity and performance may be reduced due to excessive progress of the surface crosslinking reaction.
[0154] Simultaneously, can carry out the step of forming surface crosslinking layer when the surface crosslinking agent further comprises inorganic material.As such inorganic material, can use one or more in the group being selected from by silicon dioxide, clay, aluminum oxide, silicon dioxide-alumina composite material, titanium dioxide, zinc oxide and aluminum sulfate.Inorganic material can be used in the form of powder or liquid, particularly aluminum oxide powder, silicon dioxide-alumina powder, titanium dioxide powder or nano silicon dioxide solution.Based on the base resin of 100 weight parts, the usage amount of inorganic material can be about 0.001 weight part to about 1 weight part.
[0155] In addition, the diester compound can be mixed with the base resin along with the surface crosslinking agent. The diester compound can suppress the odor of the absorbed material, thereby imparting deodorizing ability to the superabsorbent polymer.
[0156] The diester compound of one embodiment can be represented by the following chemical formula 1:
[0157] [Chemical formula 1]
[0158]
[0159] In Chemical Formula 1, n may be an integer of 1 to 10, for example, an integer of 2 to 4.
[0160] R can be C 1-20 In particular, R can be C 3-4 Straight chain or branched alkyl. For example, R can be isopropyl or isobutyl.
[0161] The diester compound may include one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate, diisobutyl glutarate and diisobutyl adipate. In particular, the diester compound may include one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate and diisobutyl adipate.
[0162] Based on 100 parts by weight of the base resin, the content of the diester compound may be 0.1 to 5.0 parts by weight. In particular, based on 100 parts by weight of the base resin, the content of the diester compound may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, or 0.4 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, 1.0 parts by weight or less, or 0.5 parts by weight or less.
[0163] In order to exhibit a target level of deodorizing ability while maintaining the unique absorption properties of the super absorbent polymer, in the present invention, it is preferred that the content of the diester compound as the deodorizing substance is within the above range.
[0164] The diester compound can be mixed with the base resin in the form of a solution or an emulsion along with a surface crosslinking agent. Alternatively, after adding the surface crosslinking agent, the diester compound can be mixed with the base resin by spraying the diester compound in a solution or emulsion state. In the case where the diester compound is used in an emulsion state, the emulsifier can be a surfactant, particularly a surfactant of natural origin, such as lecithin, etc. In this case, the diester compound can be present in the surface crosslinking layer.
[0165] Meanwhile, the mixing method of the base resin and the surface cross-linking agent may be appropriately selected without specific limitation as long as they can be uniformly mixed.
[0166] For example, a method of placing the surface crosslinking composition and the base resin in a reactor and mixing them, a method of spraying the surface crosslinking agent onto the surface of the base resin, a method of continuously feeding the base resin and the surface crosslinking agent into a continuously operated mixer and mixing them, etc. can be used.
[0167] Among them, the surface cross-linking agent can be an aqueous solution. When the solid content in the solution is more than 1 weight %, more than 3 weight %, more than 5 weight %, more than 10 weight %, and less than 50 weight %, less than 30 weight %, and less than 20 weight %, it can be appropriately and evenly dispersed in the base resin and at the same time prevent the base resin from agglomerating.
[0168] (Step 4)
[0169] Step 4 is a step for reacting the base resin with a surface crosslinking agent to form an interpenetrating polymer network on the surface of the crosslinked polymer contained in the base resin, thereby further improving the performance of the superabsorbent polymer. Through this surface modification, a surface crosslinking layer is formed on the surface of the ground base resin particles.
[0170] The formation of the surface crosslinked layer can be performed by a common method of increasing the crosslinking density of the polymer particle surface, and for example, it can be performed by mixing the ground polymer with a surface crosslinking solution containing a surface crosslinking agent and heat-treating the mixture to cause it to undergo a crosslinking reaction.
[0171] Step 4 may be performed at a temperature of about 80° C. to about 250° C. More specifically, the surface crosslinking process may be performed at a temperature of about 100° C. to about 220° C., or about 110° C. to about 200° C., or about 120° C. to about 190° C., for about 10 minutes to about 2 hours, or about 20 minutes to about 60 minutes. If the crosslinking reaction temperature is less than 160° C. or the reaction time is too short, the surface crosslinking reaction may not sufficiently occur, and thus the degree of penetration may be reduced, and if the crosslinking reaction temperature is greater than 200° C. or the reaction time is too long, the water retention capacity may be reduced.
[0172] There is no specific restriction on the heating mode of the surface cross-linking reaction. A heat transfer medium can be supplied, or a heat source can be directly supplied for heating. Among them, as the type of heat transfer medium that can be used, a heating fluid such as steam, hot air, hot oil can be used, but the present invention is not limited thereto, and the temperature of the supplied heat transfer medium can be appropriately selected by considering the mode of the heat transfer medium, the heating mode and the target temperature. At the same time, as the heat source directly supplied, electric heating and gas heating can be mentioned, but the present invention is not limited thereto.
[0173] In addition, the diester compound can be mixed with the super absorbent polymer having a surface crosslinked layer. The type, mixing amount, and mixing form of the diester compound are as described in step 3. In the case of the mixing, the diester compound can exist separately from the super absorbent polymer. In this case, the diester compound exists on the surface of the surface crosslinked layer formed during the surface crosslinking step, and therefore, the contact area with the odor increases, and the deodorizing ability can be improved.
[0174] In addition, the diester compound can be used together with the surface crosslinking agent and thus exist in the surface crosslinking layer, and then the diester compound can be mixed with the super absorbent polymer having the surface crosslinking layer. In this case, it can exist both in the surface crosslinking layer and separately from the super absorbent polymer.
[0175] In addition, one or more additives selected from the group consisting of chelating agents, iodine compounds and organic acids can be further mixed with the superabsorbent polymer having a surface crosslinked layer. Similarly, additives can be present on the surface of the surface crosslinked layer formed in the surface crosslinking step, thereby increasing the contact area with the odor and improving the deodorizing ability.
[0176] The chelating agent may be mixed with the superabsorbent polymer having a surface crosslinked layer. In the case of sanitary products containing the superabsorbent polymer composition, bacteria originating from the skin and the like may encounter the absorbed liquid to additionally generate odor through bacterial growth, but the mixed chelating agent may inhibit such bacterial growth.
[0177] The chelating agent may include a glycine (or salt) type chelating agent. In particular, the glycine (or salt) type chelating agent may include one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetate (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and their salts. More particularly, the chelating agent may be ethylenediaminetetraacetic acid (EDTA).
[0178] In particular, aminoacetate chelating agents can effectively inhibit the growth of bacteria (such as E. coli) caused by odor-generating substances. As the wearing time of the product passes, the bacterial growth is accelerated by the odor-generating substances remaining in the product, thus generating additional odor, but aminoacetate chelating agents can inhibit this bacterial growth, thereby effectively reducing the generation of additional odor.
[0179] In particular, aminoacetate chelators can capture multivalent metal components required for cell membrane growth and development, thereby effectively inhibiting bacterial growth.
[0180] The content of the chelating agent may be 0.1 to 2.0 parts by weight based on 100 parts by weight of the base resin. In particular, the content of the chelating agent may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 2.0 parts by weight or less, 1.5 parts by weight or less, or 1.0 parts by weight or less, based on 100 parts by weight of the base resin.
[0181] When used within the above content range, effective bacteria inhibition performance can be achieved without deteriorating the unique absorption performance of the super absorbent polymer, thereby significantly improving the deodorizing ability of the super absorbent polymer.
[0182] The chelating agent may be mixed in an aqueous solution in the form of a salt and used, and therefore the above content range is based on the solid content.
[0183] The iodine compound can be mixed with the superabsorbent polymer having a surface crosslinked layer. The iodine compound can be a metal iodide salt. The metal iodide salt can be added in the preparation process in the form of dissolving one or more selected from the group consisting of CuI, NaI, KI and I2 in water, or in the form of a powder obtained by drying the aqueous solution. The metal iodide salt can be added to the superabsorbent polymer together with the diester compound to impart deodorizing properties. The metal iodide salt acts on most malodorous substances and usually acts by oxidizing the malodorous substances to remove them.
[0184] Based on 100 parts by weight of the base resin, the content of the iodine compound may be 0.1 to 5.0 parts by weight. In particular, based on 100 parts by weight of the base resin, the content of the iodine compound may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, or 1.0 parts by weight or less.
[0185] The organic acid may be mixed with the super absorbent polymer having a surface cross-linked layer. The organic acid may be one or more selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid, and propionic acid. In particular, the organic acid may be citric acid. The organic acid may exhibit a deodorizing effect in the super absorbent polymer together with the diester compound.
[0186] The content of the organic acid may be 0.1 to 5.0 parts by weight based on 100 parts by weight of the base resin. In particular, the content of the organic acid may be 0.1 parts by weight or more, 0.2 parts by weight or more, 0.4 parts by weight or more, or 0.6 parts by weight or more, and 5.0 parts by weight or less, 4.0 parts by weight or less, 3.0 parts by weight or less, 2.0 parts by weight or less, or 1.0 parts by weight or less, based on 100 parts by weight of the base resin.
[0187] In the case where a deodorizing substance and additives (if necessary) and the like are hydrated and added to the super absorbent polymer having a surface cross-linked layer in the form of an aqueous solution, a drying step may be additionally performed thereafter.
[0188] Hereinafter, preferred examples are given to help understand the present invention. However, the following examples are given only as illustrations of the present invention and are not intended to limit the present invention.
[0189] Comparative Example 1
[0190] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0191] The hydrogel polymer was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0192] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0193] Comparative Example 2
[0194] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0195] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0196] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0197] After that, the surface cross-linked superabsorbent polymer was chopped (pore size 16 mm) and mixed while spraying an EDTA aqueous solution (EDTA concentration 40%) on them. EDTA was mixed so that its content was 0.6 parts by weight based on 100 parts by weight of the base resin. After that, a drying step was performed at 80° C. for 25 minutes.
[0198] Comparative Example 3
[0199] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0200] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0201] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0202] After that, the surface cross-linked superabsorbent polymer was sprayed with an EDTA aqueous solution (EDTA concentration of 40%) while being chopped (pore size of 16 mm) and mixed. EDTA was mixed so that its content was 1.0 part by weight based on 100 parts by weight of the base resin. After that, a drying step was performed at 80° C. for 25 minutes.
[0203] Comparative Example 4
[0204] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0205] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0206] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0207] After that, the surface cross-linked superabsorbent polymer was chopped (pore size 16 mm) and mixed while spraying a cyclodextrin aqueous solution (cyclodextrin concentration 10%) on them. The cyclodextrin was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin. After that, a drying step was performed at 80° C. for 25 minutes.
[0208] Comparative Example 5
[0209] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0210] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0211] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0212] After that, the surface cross-linked superabsorbent polymer was chopped (pore size 16 mm) and mixed while spraying a citric acid aqueous solution (citric acid concentration 20%) on them. The citric acid was mixed so that its content was 1.0 part by weight based on 100 parts by weight of the base resin. After that, a drying step was performed at 80° C. for 25 minutes.
[0213] Comparative Example 6
[0214] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0215] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0216] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0217] After that, the surface cross-linked super absorbent polymer was chopped (pore size 16 mm) and mixed while spraying a citric acid aqueous solution (citric acid concentration 20%) on them. The citric acid was mixed so that its content was 5.0 parts by weight based on 100 parts by weight of the base resin. After that, a drying step was performed at 80° C. for 25 minutes.
[0218] Example 1
[0219] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C.2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0220] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0221] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0222] Thereafter, while spraying a diisopropyl adipate emulsion (diisopropyl adipate concentration: 20%) and an EDTA aqueous solution (EDTA concentration: 40%) using lecithin as an emulsifier on the surface cross-linked super absorbent polymer, they were chopped (pore size: 16 mm) and mixed. Among them, diisopropyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin, and EDTA was mixed so that its content was 0.6 parts by weight based on 100 parts by weight of the base resin.
[0223] Example 2
[0224] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0225] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0226] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0227] Thereafter, while spraying a diisopropyl adipate emulsion (diisopropyl adipate concentration: 20%) and a citric acid aqueous solution (citric acid concentration: 20%) using lecithin as an emulsifier on the surface cross-linked super absorbent polymer, they were chopped (pore size: 16 mm) and mixed. The diisopropyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin, and the citric acid was mixed so that its content was 0.6 parts by weight based on 100 parts by weight of the base resin.
[0228] Example 3
[0229] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0230] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0231] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0232] After that, the surface cross-linked superabsorbent polymer was chopped (pore size 16 mm) and mixed while being sprayed with diisopropyl adipate emulsion (diisopropyl adipate concentration 20%) using lecithin as an emulsifier. The diisopropyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin.
[0233] Example 4
[0234] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0235] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0236] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0237] After that, the surface cross-linked super absorbent polymer was chopped (pore size 16 mm) and mixed while being sprayed with diisopropyl adipate emulsion (diisopropyl adipate concentration 20%) using lecithin as an emulsifier. Here, diisopropyl adipate was mixed so that its content was 1.0 part by weight based on 100 parts by weight of the base resin.
[0238] Example 5
[0239] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0240] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0241] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0242] After that, the surface cross-linked superabsorbent polymer was sprayed with a diisobutyl succinate emulsion (diisobutyl succinate concentration was 20%) using lecithin as an emulsifier, and then chopped (pore size was 16 mm) and mixed. The diisobutyl succinate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin.
[0243] Example 6
[0244] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0245] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0246] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0247] After that, the surface cross-linked superabsorbent polymer was sprayed with a diisobutyl succinate emulsion (diisobutyl succinate concentration was 20%) using lecithin as an emulsifier, and then chopped (pore size was 16 mm) and mixed. The diisobutyl succinate was mixed so that its content was 1.0 part by weight based on 100 parts by weight of the base resin.
[0248] Example 7
[0249] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0250] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0251] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0252] After that, the surface cross-linked superabsorbent polymer was chopped (pore size 16 mm) and mixed while being sprayed with diisobutyl adipate emulsion (diisobutyl adipate concentration 20%) using lecithin as an emulsifier. The diisobutyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin.
[0253] Example 8
[0254] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0255] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0256] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0257] Thereafter, while spraying a diisopropyl adipate emulsion (diisopropyl adipate concentration: 20%) and a citric acid aqueous solution (citric acid concentration: 20%) using lecithin as an emulsifier on the surface cross-linked super absorbent polymer, they were chopped (pore size: 16 mm) and mixed. The diisopropyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin, and the citric acid was mixed so that its content was 5.0 parts by weight based on 100 parts by weight of the base resin.
[0258] Example 9
[0259] 100 g of acrylic acid, 0.37 g of N,N'-methylenebisacrylamide as a crosslinking agent, 0.15 g of sodium persulfate (SPS) as a thermal initiator, 0.008 g of benzoin ether as a UV initiator, 40 g of caustic soda (NaOH) and 127 g of water were mixed to prepare an aqueous monomer composition having a monomer concentration of 45.8 wt%. The aqueous monomer composition was injected into a feed section of a polymerization reactor equipped with a continuously moving conveyor belt, and then irradiated with UV (dosage: 10 mW / cm2) using a UV irradiation device while maintaining the polymerization atmosphere temperature at 80°C. 2 ), and UV polymerization was performed for 2 minutes to prepare a hydrogel polymer.
[0260] The prepared hydrogel polymer was in the form of a sheet, which was transferred to a meat chopper and cut into 2 mm to 10 mm. The water content of the cut hydrogel polymer was 47% by weight. Subsequently, the hydrogel polymer was dried in a hot air dryer at 170° C. for 30 minutes, and the dried hydrogel polymer was ground with a pin grinder. Subsequently, the polymer of 150 μm to 850 μm was classified with a sieve to prepare a base resin.
[0261] After that, in 100 parts by weight of the above-prepared base resin, a surface crosslinking agent (2.5 parts by weight of water, 0.1 parts by weight of ethylene glycol diglycidyl ether (EX-810), 0.1 parts by weight of aluminum sulfate 18 hydrate (Al-S) and 0.1 parts by weight of silicon dioxide (Aerosil A200)) was uniformly mixed, and then a surface crosslinking reaction was performed at 140° C. for 30 minutes. After the surface treatment was completed, a super absorbent polymer having a particle size of 150 μm to 850 μm was obtained by classification with a sieve.
[0262] Thereafter, while spraying a diisopropyl adipate emulsion (diisopropyl adipate concentration: 20%) and an EDTA aqueous solution (EDTA concentration: 40%) using lecithin as an emulsifier on the surface cross-linked super absorbent polymer, they were chopped (pore size: 16 mm) and mixed. The diisopropyl adipate was mixed so that its content was 0.5 parts by weight based on 100 parts by weight of the base resin, and the EDTA was mixed so that its content was 1.0 parts by weight based on 100 parts by weight of the base resin.
[0263] Experimental example
[0264] For the superabsorbent polymer compositions prepared in Examples and Comparative Examples, properties thereof were measured as follows.
[0265] 1) Odor evaluation
[0266] 2g of each superabsorbent polymer prepared in Examples 1 to 9 and Comparative Examples 1 to 6 was placed in a 500mL glass bottle, and then 50mL of urine was added. After sealing the glass bottle, aging was performed in a constant temperature chamber for 3 hours. Wherein, the temperature of the constant temperature chamber was 35°C. After aging was completed, the degree of odor was evaluated sensoryly. A total of 9 people evaluated, and the degree of odor was evaluated as 1 to 5 points, wherein the closer the score is to 1, the smaller the odor, and the closer the score is to 5, the more serious the odor. The average value of the evaluation results of 9 people is shown in Table 1.
[0267] 2) Centrifugal Retention Capacity (CRC)
[0268] The centrifuge retention capacity of each superabsorbent polymer composition of Examples and Comparative Examples was measured by the absorbency under no load according to EDA NASP 241.3 of the European Disposables and Nonwovens Association (EDANA) standard.
[0269] In particular, a polymer classified into a particle size of 300 to 600 μm was obtained from each composition of superabsorbent polymer obtained by the examples and comparative examples. Such a polymer W0 (g, about 0.2 g) was uniformly placed in an envelope made of non-woven fabric, and the envelope was sealed and then immersed in a 0.9 wt % saline solution. After 30 minutes, the envelope was drained at 250G for 3 minutes using a centrifuge, and the weight W2 (g) of the envelope was measured. In addition, the same operation was performed using an empty envelope without a polymer, and then the weight W1 (g) at that time was measured.
[0270] Using the weight thus obtained, CRC (g / g) was confirmed by the following Mathematical Formula 1.
[0271] [Mathematical formula 1]
[0272] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1
[0273] 3) Absorption under pressure (AUP)
[0274] For each superabsorbent polymer composition of Examples and Comparative Examples, the pressure absorption rate at 0.7 psi was measured according to EDANA method WSP 242.3.
[0275] First, when measuring the pressure absorption rate, the graded polymers used for measuring CRC are used.
[0276] Specifically, a 400-mesh stainless steel wire mesh was installed at the bottom of a plastic cylinder having an inner diameter of 25 mm. Furthermore, under the conditions of room temperature and 50% humidity, W0 (g) of superabsorbent polymer was uniformly dispersed on the mesh, and a piston capable of uniformly applying a load of 0.7 psi was placed thereon, wherein a piston having an outer diameter slightly smaller than 25 mm was used so that there was no gap with the inner wall of the cylinder and the up and down movement was not hindered. At this time, the weight of the device was measured, W3 (g).
[0277] In a petri dish with a diameter of 150 mm, a glass filter with a diameter of 90 mm and a thickness of 5 mm is placed, and a 0.9 wt% saline solution is poured to the same height as the upper side of the glass filter. And, a filter paper with a diameter of 90 mm is placed on it. Then, the above-mentioned measuring device is placed on the filter paper, and the solution is absorbed under pressure for 1 hour. After 1 hour, the measuring device is lifted and the weight W4 (g) is measured. Using the measured weight, the pressure absorption rate (g / g) is calculated according to the following mathematical formula 2.
[0278] [Mathematical formula 2]
[0279] AUP(g / g)=[W4(g)-W3(g)] / W0(g)
[0280] 4) Deodorization rate
[0281] The deodorization rate was measured by an adsorption tube measurement method. To test the deodorization ability, 3-methylbutanal was selected as an aldehyde malodorous substance, diacetyl was selected as a ketone malodorous substance, and dimethyl trisulfide (DMTS) was selected as a sulfur compound malodorous substance.
[0282] -Adsorption tube measurement method: 1g of super absorbent polymer is placed in a 500mL glass bottle, and then 25mL of malodorous substances are introduced. Then, aging is performed in a constant temperature chamber for 3 hours, and then capture is performed for 20 minutes. Among them, the constant temperature chamber temperature is 35°C and the N2 flow rate is 250mL / min. The discharged odor is then adsorbed to the connected adsorption tube, and the same sample is repeated twice for capture. The capture result is confirmed by GC analysis.
[0283] - Deodorization rate (%) = {odor amount of reference sample (superabsorbent polymer of Comparative Example 1) measured by GC - odor amount of sample measured by GC} / odor amount of reference sample (superabsorbent polymer of Comparative Example 1) measured by GC × 100 (%)
[0284] The odor evaluation results, centrifuge retention capacity (CRC) and absorbency under pressure (AUP) are shown in Table 1, and the deodorization rate is shown in Table 2.
[0285] Table 1
[0286]
[0287] Table 2
[0288]
[0289] As shown in the results of Table 1, in the case of Examples 1 to 9, the deodorizing ability was excellent while the absorption ability was maintained at a similar level, compared with Comparative Example 1 containing no additive.
[0290] In addition, in the case of Comparative Examples 2 and 3 in which only a chelating agent was used without using a diester compound, the deodorizing ability tended to be lowered compared to the Examples. In the case of Comparative Examples 4 and 5 in which only cyclodextrin or citric acid was used, the deodorizing ability was low compared to the Examples. In the case of Comparative Example 6 in which a large amount of citric acid was used, although the deodorizing ability was improved to some extent compared to the other Comparative Examples, it was still inferior to Example 8 in which a diester compound, i.e., diisopropyl adipate, was used together.
[0291] As shown in the results of Table 2, Comparative Examples 1 to 6 showed very poor malodorous substance inhibition rates compared to Examples 1 to 9. Even in the case of Comparative Example 6 using a large amount of citric acid, the malodorous substance inhibition rate was similar to that of the other Comparative Examples.
Claims
1. A composition of a superabsorbent polymer, comprising: A superabsorbent polymer comprising a base resin and a surface cross-linked layer formed on a surface of the base resin, wherein the base resin comprises a cross-linked polymer formed by cross-linking polymerization of an acrylic monomer having an at least partially neutralized acid group and an internal cross-linking agent, and in the surface cross-linked layer the cross-linked polymer is additionally cross-linked by the surface cross-linking agent; as well as A diester compound represented by the following chemical formula 1, The diester compound is contained in the surface cross-linked layer of the super absorbent polymer and / or is contained separately from the super absorbent polymer: [Chemical formula 1] In Chemical Formula 1, n is an integer from 1 to 10, and R is C 1-20 Straight chain or branched alkyl.
2. The superabsorbent polymer composition according to claim 1, wherein the diester compound comprises one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate, diisobutyl glutarate and diisobutyl adipate. 3 . The superabsorbent polymer composition of claim 1 , wherein the diester compound is contained in an amount of 0.1 to 5.0 parts by weight based on 100 parts by weight of the base resin.
4. The superabsorbent polymer composition of claim 1, further comprising one or more additives selected from the group consisting of a chelating agent, an iodine compound and an organic acid.
5. The superabsorbent polymer composition of claim 4, wherein the chelating agent comprises a aminoacetic acid-based chelating agent.
6. The superabsorbent polymer composition of claim 5, wherein the aminoacetic acid chelating agent comprises one or more selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), L-glutamic acid diacetic acid (GLDA), methylglycine diacetic acid (MGDA), hydroxyethylethylenediaminetriacetic acid (HEDTA), ethanol diglycine (EDG), diethylenetriaminepentaacetic acid (DTPA) and salts thereof.
7. The superabsorbent polymer composition of claim 4, wherein the iodine compound is a metal iodide salt.
8. The superabsorbent polymer composition of claim 4, wherein the organic acid is one or more selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid and propionic acid.
9. A method for preparing a composition of a superabsorbent polymer, comprising the following steps: Step 1: In the presence of an internal crosslinking agent and a polymerization initiator, crosslinking and polymerizing an acrylic monomer having an acid group that is at least partially neutralized to form a hydrogel polymer; Step 2: drying and grinding the hydrogel polymer to prepare a base resin comprising a cross-linked polymer; Step 3: mixing a surface cross-linking agent with the base resin to prepare a mixture; and step 4: heat-treating the mixture to prepare a super absorbent polymer having a surface cross-linked layer formed on the surface of the base resin, Wherein a diester compound represented by the following Chemical Formula 1 is contained during and / or after the surface cross-linking reaction: [Chemical formula 1] In Chemical Formula 1, n is an integer from 1 to 10, and R is C 1-20 Straight chain or branched alkyl.
10. The method for preparing a superabsorbent polymer composition according to claim 9, wherein the diester compound comprises one or more selected from the group consisting of diisopropyl adipate, diisobutyl succinate, diisobutyl glutarate and diisobutyl adipate.
11. The method for preparing a superabsorbent polymer composition according to claim 9, wherein the mixing amount of the diester compound is 0.1 to 5.0 parts by weight based on 100 parts by weight of the base resin.
12. The method for preparing a superabsorbent polymer composition according to claim 9, wherein after step 4, one or more additives selected from the group consisting of a chelating agent, an iodine compound and an organic acid are mixed with the superabsorbent polymer having a surface cross-linked layer.
13. The method for preparing a superabsorbent polymer composition according to claim 12, wherein the chelating agent comprises a aminoacetic acid-based chelating agent.
14. The method for preparing a superabsorbent polymer composition according to claim 12, wherein the iodine compound is a metal iodide salt.
15. The method for preparing a superabsorbent polymer composition according to claim 12, wherein the organic acid is one or more selected from the group consisting of citric acid, acetic acid, formic acid, fumaric acid, lactic acid and propionic acid.
Citation Information
Patent Citations
Substrate processing method and substrate processing apparatus
KR1020230020907A